Strategi Dakwah Takmir Masjid Husnul Khotimah Sambonggede Merakurak Tuban Dalam Meningkatkan Antusias Shalat Subuh Berjamaah - Muhammad Maftuh Afnan; Aflachal Muthowah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
The morning prayer is one of the most fundamental obligatory prayers for Muslims, and performing it in congregation is one of the parameters of the greatness of Muslims in a region and era. In fact, in practice the quantity of congregation in carrying out the morning prayer can be used as an indicator of the robustness of Muslims. One of the strategies carried out by the takmir of the mosque is by serving sticky rice and bottled drinks after the morning prayer in congregation at the mosque. So with this research it is intended to find out the Da'wah Takmir Strategy of the Husnul Khotimah Sambonggede Mosque in Improving Congregational Morning Prayers. The goal to be achieved in this research is to find out how the Da'wah Takmir Strategy of the Husnul Khotimah Mosque in increasing congregational dawn prayers at the mosque and knowing what the supporting and inhibiting factors are. This research was conducted at the Husnul Khotimah Sambonggede Mosque. This study uses a qualitative method with a descriptive approach. This study used data collection techniques in the form of interviews, observation and documentation. The number of informants is 1 chairman of the Mosque Takmir 2 mosque administrators 3 congregations or the community. The results of this study indicate that the da'wah strategy of takmir at the Husnul Khotimah mosque is able to play a role in the Sambonggede village community where the mosque administrators are able to make new breakthroughs in increasing the congregation of dawn prayers, besides that it can also prosper the mosque as the central place of religion for today's Muslims. Mosque administrators are able to create three aspects that can inspire community enthusiasm in the form of spiritual, social, and economic aspects.